Structure elucidation of antiplasmodial sesquiterpene lactones from Vernonia staehelinoides and Oncosiphon piluliferum - Vleggaar, Robert (University of Pretoria, 2013)
Dissertation (MSc (Chemistry))--University of Pretoria, 2007.